Broadband Low-Profile Dipole Antenna with Parasitic Patches and Folded Strips - Kedze, Kam Eucharist; Wang, Heesu; Park, Ikmo (2018 IEEE Antennas and Propagation Society International Symposium and USNC/URSI National Radio Science Meeting, APSURSI 2018 - Proceedings, 2018)
This paper presents the design of a broadband low-profile dipole antenna. The antenna structure consists of a radiating dipole with folded parasitic strips above four parasitic patches on a perfect electric conductor ground plane. The placement of folded parasitic strips in a circle around the dipole generates extra resonance and significantly improves the antenna's impedance and gain bandwidths. The overall dimensions of the antenna are 120 mm × 120 mm × 16.3 mm (0.66λ o x 0.66λ o x 0.09λ o at 1.66 GHz), and the antenna has a| S 11 | < -10 dB impedance bandwidth of 1.46-1.87 GHz (24.6%), a broadside gain of 8.37-8.84 dBi, and a radiation efficiency> 98%.
Keywords: Broadband; Impedance bandwidths; Low-profile; Low-profile dipole antennas; Parasitic patch; Parasitic strips; Perfect electric conductor; Radiation efficiency; Broadband; folded parasitic strip; low-profile; parasitic patch